The development of a school principal leadership model oriented towards professional performance. - Dwi Rulismi; Mesterjon Mesterjon; Syukri Hamzah (Universitas Negeri Semarang, 2023)
A leadership model for school principals that is oriented towards professional performance can enhance the quality of education and requires support from high-quality human resources. The development of human resources is a process of enhancing individuals' abilities to compete in the current era of technological advancements, known as the Industry 4.0, in order to improve the quality of education. Leadership models come in various styles, and one of them is the ACL (Action Centered Leadership) style. In this research, a qualitative approach with weighting was used. Data was collected through observation, documentation, and questionnaires. The data analysis in this study involved analyzing the development of a school principal leadership model using the ACL leadership style. The indicators included discipline, teamwork ability, collaborative cooperation, and adaptability in communication. The role of school leadership is crucial in communicating the organizational performance needs of the school and implementing the predetermined school principal's work programs. Effective leadership by school principals is essential in organizing and leading educational institutions.